The zebrafish orthologue of the human hepatocerebral disease gene MPV17 plays pleiotropic roles in mitochondria - Laura Martorano; Margherita Peron; Claudio Laquatra; Elisa Lidron; Nicola Facchinello; Giacomo Meneghetti; Natascia Tiso; Andrea Rasola; Daniele Ghezzi; Francesco Argenton (The Company of Biologists, 2019)
Mitochondrial DNA depletion syndromes (MDS) are a group of rare autosomal recessive disorders with early onset and no cure available. MDS are caused by mutations in nuclear genes involved in mitochondrial DNA (mtDNA) maintenance, and characterized by both a strong reduction in mtDNA content and severe mitochondrial defects in affected tissues. Mutations in MPV17, a nuclear gene encoding a mitochondrial inner membrane protein, have been associated with hepatocerebral forms of MDS. The zebrafish mpv17 null mutant lacks the guanine-based reflective skin cells named iridophores and represents a promising model to clarify the role of Mpv17. In this study, we characterized the mitochondrial phenotype of mpv17−/− larvae and found early and severe ultrastructural alterations in liver mitochondria, as well as significant impairment of the respiratory chain, leading to activation of the mitochondrial quality control. Our results provide evidence for zebrafish Mpv17 being essential for maintaining mitochondrial structure and functionality, while its effects on mtDNA copy number seem to be subordinate. Considering that a role in nucleotide availability had already been postulated for MPV17, that embryos blocked in pyrimidine synthesis do phenocopy mpv17−/− knockouts (KOs) and that mpv17−/− KOs have impaired Dihydroorotate dehydrogenase activity, we provided mpv17 mutants with the pyrimidine precursor orotic acid (OA). Treatment with OA, an easily available food supplement, significantly increased both iridophore number and mtDNA content in mpv17−/− mutants, thus linking the loss of Mpv17 to pyrimidine de novo synthesis and opening a new simple therapeutic approach for MPV17-related MDS.